(untitled) (Al-Academy, 2020)
This research aims to realize one of the pillars of Saudi vision (2030) through searching for new sources full of material folklore that had not previously been studied, so this study will study folk motifs engraved on the doors and windows in the Bani Amru Center in the Al-Namas governorate that is situated in the Asir region , in particular the tribe (Bani Rafe), before being disappeared due to the abandonment of the old architecture by the people of the region and their fascination with modern architecture, therefore I must as one of the people of the region document and preserve that through studying, analyzing, classifying it, then inspiring typed paintings using a new technical typing that have not yet been used in the Kingdom of Saudi Arabia on a large scale, in spite of it is not recently used outside the Kingdom, which is called (monotype), and this technology is known as monotype, where no two similar copies thereof can be taken and it is one of the new typing technologies that is characterized by soft and color surfaces. The research uses the descriptive analytical approach to folk motifs in the region and the experimental approach by implementing five typed paintings inspired by folk motifs in the region